Pengaruh Penggunaan Minyak Serai (Cymbopogon nardus L Oil) terhadap Penurunan Intensitas Nyeri Artritis Rheumatoid pada Lansia - Dian Utama Pratiwi Putri; Wayan Sri Astuti (Politeknik Kesehatan Tanjung Karang, 2020)
Rheumatoid arthritis is an autoimmune disease and this means joint inflammation. The objective of this research was to find out the influence of Cymbopogon oil (Cymbopogon nardus L) on the elderly’s rheumatoid arthritis pain intensity reduction in Way Panji public health center of Sidoharjo village in Way Panji sub-district of South Lampung in 2018. This was pre-experimental research with one group pretest and posttest design. 67 samples were taken by using stratified random sampling. Data were collected using interviews and observations by using a numeric rating scale (NRS) for pain intensity. The result showed that before and after Cymbopogon oil administration the NRS were 2,87 and 1,37 respectively. The independent t-test result showed rheumatoid arthritis pain intensity differences before and after Cymbopogon oil administration with a t-value of 24.254 and a significance value of 0.000. This indicated that Cymbopogon oil could be used as one of the alternatives for reducing pain intensity. The conclusion was that there was a significant difference in pain intensity before and after using Cymbopogon oil at rheumatoid arthritis patients in Way Panji public health center of Sidoharjo village in South Lampung (p-value 0,000). The researcher expects this research result can be used as an information source and reference for autonomous intervention for rheumatoid arthritis patients.